Research Progress on Shear Mechanism and Size Effect of UHPC Beams without Web Reinforcement - Dai, Jinjie; Chen, Tuoting (International Core Journal of Engineering, 2025)
This study provides a comprehensive review of the shear mechanisms and size effects in Ultra-High Performance Concrete beams without web reinforcement. UHPC, which is distinguished by its excellent mechanical properties and dense microstructure, displays distinct shear characteristics when compared to traditional concrete. Both experimental and theoretical investigations have revealed that although UHPC beams benefit from enhanced shear capacity due to steel fiber reinforcement, they are still influenced by size effects. Specifically, the nominal shear stress tends to decrease as the beam depth increases. Notably, several key findings have emerged: fiber content enhances shear strength but does not eliminate size effects; parameters such as shear-span ratio, fiber type, and reinforcement configuration play a significant role in determining shear performance; existing design codes need to be refined to better account for the unique size effects associated with UHPC. In recent years, advancements have led to the development of analytical models that incorporate fiber contributions and arching action. These models have been validated through extensive testing, offering a more accurate basis for the design and analysis of UHPC beams.